Asymmetric charge injection barrier yields high rectification in a rhenium(I)-organometallic compound - Rajbangshi, Subas; Pal, Nila; Gupta, Ritu; Rahman, Robinur; Sachan, Pradeep; Nesterov, Vladimir N.; Roy, Lisa; Ghosh, Shishir; Zharnikov, Michael; Mondal, Prakash Chandra (Journal of materials chemistry. C, Materials for optical and electronic devices, 2025)
Electrical rectification is an important electronic function in molecular electronics. Many organic molecules and metal complexes have been studied in this context, assisted by analysis of the related charge transport mechanisms. However, Re(I)-organometallic compounds, which hold many opportunities in electronic functions, have not been explored in electronic circuitry so far. To this end, the present study focuses on emulating electrical current rectification by π-stacked Re(I) organometallic compounds embedded between p-doped Si and indium tin oxide electrodes in a two-terminal junction configuration. Among the tested compounds, viz. [Re(CO)4(PPh3){κ1-(N)-saccharinate}] (1) and [Re(CO)3(κ2-phen){κ1-(N)-saccharinate}] (2), the latter demonstrates a remarkable electrical current rectification ratio of ≈4 × 103 at ±2.0 V at room temperature. The model device, composed of 2, demonstrates proficient alternating current (AC) to direct current (DC) conversion at a frequency of up to 1 kHz, tested in a half-wave rectifier configuration. Temperature-dependent experimental current-voltage analysis implies the primary role of activated long-distance hopping for the charge transport and the asymmetric charge injection barrier heights at both electrode interfaces for current rectification. The above results lay the groundwork for using diverse organometallic compounds as circuit elements in nanoelectronic devices for specific electronic functions.
Gesehen am 28.01.2026